Kepadatan larva nyamuk Aedes spp. di Kelurahan Mapanget Barat Kota Manado - Rey, Gloria Pinly; Pijoh, Victor David; Wahongan, Greta Jane Pauline (UNIVERSITAS SAM RATULANGI, 2024)
Background: Dengue hemorrhagic fever (DHF) is an infectious disease transmitted through the Aedes spp. mosquitoes. Based on data from Manado City’s Health Department, the Mapanget District is one of the areas with a relatively high number of DHF cases in Manado City. The Mapanget Barat Village is part of the Mapanget District and also contributes to DHF cases every year. Therefore, the vector's data of larval density is needed as an effort to prevent transmission of the dengue virus. Aim: determine the larval density of Aedes spp. mosquito in Mapanget Barat Village, Manado City. Methods: This study is a descriptive research with a cross-sectional method. Research sample consists of larvae collected from 100 households in Mapanget Barat Village. The data analysis is conducted by calculating the House Index (HI), Container Index (CI), Breteau Index (BI), and Larvae Free Index (LFI). Result: Based on survey of 100 houses, HI value of 24% was obtained. The percentage of larvae in the TPA breeding places is 65.62%, and in non-TPA breeding places is 34.38%. The types of containers that found positive for larvae were buckets for 10.93%, bathtubs for 7.14%, drums for 8.48%, followed by used buckets at 14.29%, and flower pots at 8.33%. The identification results indicate that all larva samples belong to the Aedes aegypti species. Results of the CI calculation are 8.91%, the BI is 32%, and the LFI is 76%. Conclusion: The larval density of Aedes spp. mosquito in Mapanget Barat Village is on the moderate level, categorizing it as an area with moderate risk for the spread of DHF. Keywords: larval density, dengue hemorrhagic fever, Aedes spp. mosquito larvae